Numerical simulation of the effect of shale lamination structure on hydraulic fracture propagation behavior - Xun Gong; Zhijun Jin; Xinhua Ma; Yuyang Liu (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Hydraulic fracturing technology is important in developing low-porosity and low-permeability oil and gas reservoirs. However, the presence of discontinuities such as natural fractures (NF), lithological interfaces, and bedding (B) in rocks seriously affects the propagation paths of hydraulic fractures (HF) and their geometrical morphology. Therefore, this study proposes a numerical model based on the finite element method (FEM) for indoor hydraulic fracturing scale and simulates the interaction between hydraulic fractures and bedding during the fracturing process. The results show that when the hydraulic fracture extends to the bedding, five types of propagation behaviors may occur: arresting, turning, turning and then crossing, turning while crossing, and crossing directly, which are controlled by factors such as the geostress, the mechanical properties of the rock matrix and bedding, the bedding inclination, and its density, etc. During the fracturing process, the increase of elastic modulus ratio between the rock matrix and bedding and bedding inclination angle is conducive to the hydraulic fracture turning along the bedding; the increase of principal stress difference and bedding density is conducive to the hydraulic fracture directly passing through the bedding. When the inclination angle of the bedding distributes from 15° to 60°, the hydraulic fractures will first turn along the bedding when they extend to the bedding, and then extend for a certain distance before passing through the bedding and the distance of extension is positively correlated with the inclination angle of the bedding. The hydraulic fracture extension criterion in the bedding was established by using the ratio of elastic modulus of the rock matrix and bedding, geostress, and bedding inclination, and the results of the study will guide the design and optimization of fracturing in shale with bedding development.